Effects of Germanium substitutions at Cu/Sr sites on fluctuation induced conductivity and interplanar coupling of TI₀.₈₅Cr₀.₁₅Sr₂CaCu₂O₇₋₈ superconductor / Azliza Ali Yusuf - Ali Yusuf, Azliza (2011)
This thesis describes the effects of Germanium (Ge) substitutions at Cu/Sr sites on fluctuation induced conductivity and interplanar coupling of T11212 layered structure. Two series of T11212 superconductors were synthesized from TI₀.₈₅ Cr₂ CaCu₂₋ₓGeₓO₇₋₈ (х=0-0.6) and TI₀.₈₅ Cr₀.₁₅ Sr₂ CaCu₂₋ₓGeₓO₇₋₈ (y=0-0.3) nominal starting compositions using the conventional solid state method. Substitution of Ge⁴⁺ in place of Cu in TI₀.₈₅ Cr₂ CaCu₂₋ₓGeₓO₇₋₈ (х=0-0.6) series showed initial increase in zero critical temperature value, Tc zero from 98 K (x=0) to 100 K (x=0.1) and in the range of 85-86 K for x= 0.2-0.3. The slow decrease in Tc zero is unexpected as tetravalent Ge⁴⁺ substitution is expected to strongly reduce hole concentration in the samples and suppress Tc zero.While for substitution of Ge⁴⁺ in place of Sr in TI₀.₈₅ Cr₀.₁₅ Sr₂ CaCu₂₋ₓGeₓO₇₋₈ (y=0-0.3) series, electrical resistance measurements showed the zero critical temperature value, Tc zero were in the range of 90-98 K for.y=0 - 0.15 and in range of 60-78 K forj;= 0.2-0.3. Analysis of excess conductivity behavior based on Aslamazov-Larkin model for the Ge free compound, revealed a 2D fluctuation behavior. However, substitution of Ge in both of the series induced 2D to 3D transition behavior with the highest transition temperature, T2D-3D observed at x= 0.10 and y= 0.10 samples. The analyses of Fourier transformation infrared (FTIR) and X-ray diffraction (XRD) data indicate increasing CuO inter-plane coupling with Ge substitution at both Cu and Sr-sites. The increment was suggested to cause sustenance of the high Tc zero and metallic normal state behavior for x= 0-0.30 and y= 0.03-0.15 samples. This is supported by the excess conductivity analysis using the Lawrence Doniach model which also indicates an increase in the inter-plane coupling (J) values. It was suggested that the increase in inter-plane coupling may enhance correlation between the carrier of the superconducting samples which then decrease the anisotropy and resulted to better superconducting properties of the samples.